2015
DOI: 10.1016/j.matdes.2014.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser melting of AlSi10Mg alloy: Process optimisation and mechanical properties development

Abstract: a b s t r a c tThe influence of selective laser melting (SLM) process parameters (laser power, scan speed, scan spacing, and island size using a Concept Laser M2 system) on the porosity development in AlSi10Mg alloy builds has been investigated, using statistical design of experimental approach, correlated with the energy density model. A two-factor interaction model showed that the laser power, scan speed, and the interaction between the scan speed and scan spacing have the major influence on the porosity dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
401
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 969 publications
(469 citation statements)
references
References 17 publications
14
401
1
5
Order By: Relevance
“…• Al-Si alloys: Due to their attractive combination of low weight, high heat conductivity and mechanical properties, Al-Si alloys (AlSi10Mg [151][152][153][154][155][156][157] and Al-12Si [158,159]) have wide applications in aerospace, automotive industries as heat exchangers. AlSi10Mg and Al-12Si are hypoeutectic alloys whose mechanical properties are largely dependant on the morphology of eutectic silicon.…”
Section: Materials Manufactured With Slmmentioning
confidence: 99%
“…• Al-Si alloys: Due to their attractive combination of low weight, high heat conductivity and mechanical properties, Al-Si alloys (AlSi10Mg [151][152][153][154][155][156][157] and Al-12Si [158,159]) have wide applications in aerospace, automotive industries as heat exchangers. AlSi10Mg and Al-12Si are hypoeutectic alloys whose mechanical properties are largely dependant on the morphology of eutectic silicon.…”
Section: Materials Manufactured With Slmmentioning
confidence: 99%
“…Compared with the powder induced porosity, the process induced one has received more research attention since it can be eliminated by tuning the process parameters properly. The high viscosity [31] and the solubility decrease [32] of molten powder materials, improper laser scanning strategies [21], laser power, speed [33], spot diameter, powder layer thickness, preheat temperature [23], hatching spacing [24] would detrimentally cause porosity since low energy input would decrease the area of melt pool and lead to incomplete consolidation [25]. The porosity will continuously have influence on surface roughness and finally geometrical accuracy [20,31,[34][35][36].…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…observed the same trend using a different material, namely a A1Si10Mg alloy. They concluded that the porosity increase above a critical energy density was caused by vapourisation [30].…”
Section: Density and Porosity Measurementsmentioning
confidence: 99%
“…al. reported the major influence on the SLS build arising from the interaction between laser power, scan speed and scan spacing [30]. From the literature studies, it was concluded that laser power and scan speed are the crucial parameters in determining the porosity of the fabricated parts.…”
Section: Introductionmentioning
confidence: 99%